Position and ranking influence in padel: somatic anxiety and self-confidence increase in competition for left-side and higher-ranked players when compared to pressure training - Conde-Ripoll, Rafael; Escudero-Tena, Adrián; Bustamante-Sánchez, Álvaro (Frontiers in Psychology, 2024)
This study aimed to analyze the differences in the precompetitive anxiety and self-confidence according to the side of play, the ranking and the match outcome, under different competitive scenarios, in high level men’s padel players from Finland who trained under pressure prior to the competition. 10 men’s padel players (28.60 (4.17) years old) from the highest category participated in the research. The CSAI-2R (Competitive State Anxiety Inventory-2 Revised) and STAI-S (State–Trait Anxiety Inventory – State) questionnaires were used and descriptive and inferential analyzes were performed, including Mann–Whitney’s U tests. The findings illuminate that, across the player spectrum, somatic anxiety and self-confidence levels are higher before competition compared to training matches. This trend holds true for left-side, higher-ranked and match winning players. Even lower-ranked players exhibit heightened self-confidence preceding competitions. These insights offer valuable considerations for players, coaches, and sports psychologists, fostering a deeper understanding of the intricate interplay between pressure training, competition, and the athlete’s psychological landscape.